2003
DOI: 10.1007/s10254-002-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Transport of organic anions across the basolateral membrane of proximal tubule cells

Abstract: Renal proximal tubules secrete diverse organic anions (OA) including widely prescribed anionic drugs. Here, we review the molecular properties of cloned transporters involved in uptake of OA from blood into proximal tubule cells and provide extensive lists of substrates handled by these transport systems. Where tested, transporters have been immunolocalized to the basolateral cell membrane. The sulfate anion transporter 1 (sat-1) cloned from human, rat and mouse, transported oxalate and sulfate. Drugs found ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
204
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(214 citation statements)
references
References 187 publications
(319 reference statements)
8
204
0
2
Order By: Relevance
“…A number of studies on intact renal proximal tubules (5,7) and renal proximal tubule cells in culture (9,33) have demonstrated PKC-dependent downregulation of the basolateral uptake of organic anions into cells, most likely mediated (at least in part) by the PAH-dicarboxylate exchanger OAT1 (2). How this downregulation is achieved is still unknown, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on intact renal proximal tubules (5,7) and renal proximal tubule cells in culture (9,33) have demonstrated PKC-dependent downregulation of the basolateral uptake of organic anions into cells, most likely mediated (at least in part) by the PAH-dicarboxylate exchanger OAT1 (2). How this downregulation is achieved is still unknown, however.…”
Section: Discussionmentioning
confidence: 99%
“…The renal secretory organic anion transport pathway plays an important role in the elimination of a variety of potentially toxic environmental chemicals, such as phenoxyacetate herbicides and fungicides, as well as anionic drugs, including ␤-lactam antibiotics, cytostatic agents, diuretics, and antiviral drugs (1,2). The importance of this pathway is exemplified by the increased toxicity of methotrexate when it is coadministered with nonsteroidal anti-inflammatory drugs (3), which compete for the same elimination pathway (4) and thus lead to higher serum methotrexate concentrations (3).…”
mentioning
confidence: 99%
“…The organic anion transporters OAT1 and OAT3 are localized at the basolateral membrane of proximal tubule cells and mediate the concentrative uptake of their substrates from blood into renal proximal tubule cells, which is the rate-limiting step in this excretion system [14]. Genes of both transporters were cloned from several species, including rat and man, and are highly conserved across species [14,15]. Both transporters show overlapping substrate specificities and share the driving force -exchange of organic anions against intracellular α-ketoglutarate.…”
Section: Introductionmentioning
confidence: 99%
“…VanWert et al found that ciprofloxacin was transported by OAT3 and ciprofloxacin, norfloxacin, ofloxacin and gatifloxacin inhibited OAT3 [31]. Ciprofloxacin did not interact with OAT1, while probenecid inhibits both OAT1 and OAT3 [31,32]. Also, involvement of OCT was reported for ciprofloxacin [31] as for probenecid.Therefore an OAT, e.g.…”
Section: Discussionmentioning
confidence: 99%